The Role of Tapak Suci in the Mental Health of Generation Z at Muhammadiyah University of Surabaya: A Psychological and Spirituality Perspective - Gilang Pandawa; M. Maulana Mas'udi; Muh. Wahid Nur Tualeka (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The purpose of the study was to determine the Role of Tapak Suci in the Mental Health of Generation Z at the University of Muhammadiyah Surabaya: Psychological and Spirituality Perspectives. This study uses a descriptive qualitative research method. This study was conducted in June 2025. The location of the study is at the University of Muhammadiyah Surabaya. Then interviews were conductessd with the Tapak Suci Supervisor and 2 UM Surabaya students. In addition to using interviews, to strengthen the results of the study, data collection procedures were used consisting of questionnaires, observations, and documentation. Checking the validity of the data using triangulation techniques, namely using source triangulation and technique triangulation. The steps that will be taken in analyzing the data are: data reduction, data presentation, and verification or conclusions (conclusion drawing). The results of this study indicate that the Role of Tapak Suci in the Mental Health of Generation Z at the University of Muhammadiyah Surabaya: Perspective and Spirituality, namely Tapak Suci is able to make a significant contribution to the development and formation of character, mental health, and spirituality of students. Through character education, physical training, and spiritual guidance, Tapak Suci not only equips students with self-defense skills, but also instills moral values, honesty, responsibility, and work ethic that are important for self-development and mental resilience. Tapak Suci activities have been proven to help students manage stress, increase self-confidence, improve mood, and provide a sense of calm after facing academic pressure. In addition, the integration of Islamic values and spirituality in every training and education and training can also strengthen students' mental resilience, helping them face the various challenges of campus life and the transition to adulthood.